Canadian justice, indigenous injustice: the Gerald Stanley and Colten Boushie case - Roach, Kent (McGill-Queen's University Press, 2019)
In August 2016 Colten Boushie, a twenty-two-year-old Cree man from Red Pheasant First Nation, was fatally shot on a Saskatchewan farm by white farmer Gerald Stanley. In a trial that bitterly divided Canadians, Stanley was acquitted of both murder and manslaughter by a jury in Battleford with no visible Indigenous representation. In Canadian Justice, Indigenous Injustice Kent Roach critically reconstructs the Gerald Stanley/Colten Boushie case to examine how it may be a miscarriage of justice. Roach provides historical, legal, political, and sociological background to the case including misunderstandings over crime when Treaty 6 was negotiated, the 1885 hanging of eight Indigenous men at Fort Battleford, the role of the RCMP, prior litigation over Indigenous underrepresentation on juries, and the racially charged debate about defence of property, self-defence, guns, and rural crime. Drawing on both trial transcripts and research on miscarriages of justice, Roach looks at jury selection, the controversial "hang fire" defence, how the credibility and beliefs of Indigenous witnesses were challenged on the stand, and Gerald Stanley's implicit appeals to self-defence and defence of property, as well as the decision not to appeal the acquittal. Concluding his study, Roach asks whether Prime Minister Justin Trudeau's controversial call to "do better" is possible, given similar cases since Stanley's, the difficulty of reforming the jury or the RCMP, and the combination of Indigenous underrepresentation on juries and overrepresentation among those victimized and accused of crimes. Canadian Justice, Indigenous Injustice is a searing account of one case that provides valuable insight into criminal justice, racism, and the treatment of Indigenous peoples in Canada.